A method of forecasting the weather associated with western disturbances (MAUSAM, 1978)
In the present study the authors have presented a method of forecasting the weather associated with western disturbances using the lower tropospheric wind flow pattern. For this purpose, the lower tropospheric winds over the country at two levels were studied -(i) the wind pattern at 0.9 kill and (ii) the position of subtropical ridge at 850 mb level. On the basis of the wind pattern at these two levels, the weather associated with western disturbances is divided into six broad categories. These are explained with the help of model diagrams. The conclusions have been drawn based on daily data for the months December to February 1960.1973.This method is especially suitable when data over Pakistan, Afghanistan and neighbourhood are not available. It can also be used as an aid in forecasting the arrival of western disturbances and their associated weather over Indian region.